IMPLEMENTASI MODEL PEMBELAJARAN HAND ON ACTIVITY TERHADAP SISWA KELAS IV SEKOLAH DASAR - Haykal, Rafi; Zakiah, Linda; Sakmal, Juhana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning motivation and high absenteeism among fourth-grade students at SDN Rawabuaya 03 Pagi. Preliminary observations revealed that the lack of student engagement was caused by monotonous, teacher-centered learning methods that failed to stimulate students’ curiosity and participation. This study aims to describe the implementation of the Hand on Activity learning model and analyze its impact on students' motivation and learning outcomes. This research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The research subjects consisted of the principal, classroom teacher, and fourth-grade students.. The results of the study indicate that the Hand on Activity learning model significantly increases student participation, motivation, and understanding. Students are more enthusiastic about participating in learning when directly involved in practical activities rather than passive listening. Teachers utilize learning tools such as group discussions, experiments, and real-life simulations to create a more interactive and enjoyable learning environment. Additionally, involving parents through communication before the learning process helps students prepare better for classroom activities. Despite some challenges, such as limited learning media and facilities, the application of the Hand on Activity model proves effective in enhancing cognitive, psychomotor, and social skills. This research concludes that the Hand on Activity model is highly effective for primary education as it fosters active learning, improves student attendance, and enhances learning outcomes. Therefore, this model is recommended for wider implementation in elementary schools to create a more engaging and meaningful learning process